A data model for multimedia database of Malaysian cultural heritage artefacts management - Ismail, Mohd Norasri (2007)
Multimedia is one of the much talked fenomena in the field of information technology. CUlTently, vast amount of multimedia content are created for multiple purposes pariicularly to convey information effectively. Cultural heritage domain is also benefited from multimedia teclmology where multimedia content is used for depicting tangible and intangible ariefacts and for infonnation dissemination. However, the vast amount of multimedia especially in the cultural heritage domain needed a special data model to cater the need of both collection management and digital multimedia content. There are finished and cUlTently active research activities regarding multimedia database for cultural heritage application tlu·oughout the world especially in Europe. The problem is there is no research has been done in the local context especially in the field of multimedia database application in the cultural heritage domain. There are also no data model that support both information of cultural heritage and multimedia data in the local context. The intention of this research is to design a data model for multimedia database of cultural heritage artefact management as well as tries to fill the gap of cultural heritage dan multimedia database research in the context of Malaysia. A multiple case studies is conducted to gather information and requirements from the local museums governing organizations. Literature study also conducted to gain information regarding the guidelines, standards and reference models which is relevant to this research. From the requirements gathering as well as literature reviews, the logical and physical data for multimedia database of Malaysia cultural heritage ariefacts management was designed and modelled. The data model employ a hybrid of museum metadata standard known as ISO 21127:2006 or CIDOC Conceptual Reference Model (CRM) and multimedia database standards known as MPEG-7. This research also employ a model developed by Jane Hunter (2002) where combination between CRM and MPEG-7 for describing multimedia in museums is made possible.